Trusted infrastructure needs DINIvolution – the DINI certificate for Open Access publishing services: an innovative model and use case for building and maintaining sustainable open infrastructure (PUBMET, 2023)
Research information infrastructure services require transparent criteria and guidelines to be considered trustworthy, i.e. sustainable, interoperable and ready for future challenges. The DINI Certificate for Open Access Publication Services (an English version is currently in preparation) supports these requirements. The community-developed, noncommercial certificate paves the way for open scholarly communication and supports the prerequisites for the free availability of scholarly information as an essential element of future-oriented research-related services. Launched in 2004 and now in its 7th revised version, the DINI certificate has undergone dozens of successful certification processes, and is still unique and can be considered a de facto standard for publishing services, at least in Germany, and a role model for other countries. It is therefore recommended as a guide for publication services by the German Research Foundation (DFG).The DINI Certificate is managed by a team of information experts from research libraries, research organisations and software developers who are organised in the “Electronic Publishing” working group of DINI e.V. DINI or the German Initiative for Networked Information (Deutsche Initiative für Netzwerkinformation) promotes the development of interoperable open and trustworthy information infrastructures and services at research institutions.The DINI Certificate is based on an elaborate set of criteria that takes into account international standards and reflects the current state of technical, organisational and editorial requirements. For certified institutions, the DINI certificate provides a quasiguarantee that their service complies with the requirements of open science and will continue to do so. For others, it provides guidance on implementing a state-of-the-art service. Feedback from the interested community is collected through an open call for comments and taken into account in the revision processes.In the latest certificate (2022), the focus is on supporting users as authors and recipients, the requirements of open science, the sustainability of the service infrastructure, and the desired internationalisation. As a first step towards internationalisation, the certificate has been extended to include the specific requirements for certification of Austrian publication services. Complementary tools and measurements support the effectiveness of the certificate.This presentation will highlight the “DINIverse” − the DINI Certificate and its complementary tools − as a central instrument and inspiration for establishing and maintaining trustworthy Open Access publishing services. In three chapters it will give a brief overview of the origin of the certificate and the continuous adoption of new established requirements as essential parts of the “DINIvolution”, the related workflows, the benefits for users as well as the related services and projects: e.g. supporting tools like the DINI OAI validator, a dynamic overview of publishing services from Germanspeaking countries developed in cooperation with BASE - Bielefeld Academic Search Engine as well as a specialised vocabulary to support compliance with international standards.
Keywords: open access; open science; repository; standardisation; quality seal